1989
DOI: 10.1210/mend-3-10-1666
|View full text |Cite
|
Sign up to set email alerts
|

Activin Stimulation of Inhibin Secretion and Messenger RNA Levels in Cultured Granulosa Cells

Abstract: Recent reports suggest that activin (the dimer of inhibin beta subunits with FSH-releasing activity) has specific receptors on ovarian granulosa cells. The present study examined the effects of purified porcine activin on inhibin secretion and mRNA levels in granulosa cells obtained from immature, estrogen-treated rats. Cells were cultured for 48 h in culture media, or media containing FSH (10 ng/ml) and/or activin (30 ng/ml). Western blot analyses performed with affinity-purified antisera to inhibin alpha- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
29
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(38 citation statements)
references
References 40 publications
9
29
0
Order By: Relevance
“…These data showed that the levels of inhibin-A and subunit could be directly compared, which is perhaps not surprising given that the assays share a common standard and coating antibody. Gel filtration confirmed previously published observations (Bicsak et al 1988, LaPolt et al 1989 that the predominant inhibin forms in FSH-stimulated granulosa cell-conditioned media are 31 k inhibin and molecular weight forms of the subunit greater than 31 k. However, unlike Bicsak et al (1988), we were able to detect 31 k inhibin in basal granulosa cell-conditioned media (data not shown). This difference probably reflects the different methodologies employed and their relative sensitivities.…”
Section: Discussionsupporting
confidence: 91%
“…These data showed that the levels of inhibin-A and subunit could be directly compared, which is perhaps not surprising given that the assays share a common standard and coating antibody. Gel filtration confirmed previously published observations (Bicsak et al 1988, LaPolt et al 1989 that the predominant inhibin forms in FSH-stimulated granulosa cell-conditioned media are 31 k inhibin and molecular weight forms of the subunit greater than 31 k. However, unlike Bicsak et al (1988), we were able to detect 31 k inhibin in basal granulosa cell-conditioned media (data not shown). This difference probably reflects the different methodologies employed and their relative sensitivities.…”
Section: Discussionsupporting
confidence: 91%
“…This interpretation is supported by the strong correlation between activin A and either inhibin A or follistatin in all three gestational tissues, which suggest that the synthesis of these three polypeptides is regulated in a similar fashion in response to regulatory signals in these tissues. Indeed, activin itself may be the common link, since inhibin and follistatin synthesis and secretion have been shown to be regulated by activin in a number of tissues (La Polt et al 1989, Bilezikjian et al 1993, Song et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…The ACTH-induced shift from primarily DHAS production to increased cortisol production in the fetal zone is analogous to the shift in steroidogenesis that occurs postnatally. Activin (33). This difference may reflect species-specific, organ-specific, and/or developmentally dependent regulation ofsubunit production.…”
Section: Discussionmentioning
confidence: 99%